Impact of an educational DVD on anxiety and glycaemic control in women diagnosed with gestational diabetes mellitus (GDM): A randomised controlled trial. (April 2017) - Draffin, Claire R.; Alderdice, Fiona A.; McCance, David R.; Maresh, Michael; Harper, Roy; Patterson, Christopher C.; Bernatavicius, Giovanna; Brennan, Sarah F.; Gough, Aisling; McSorley, Oonagh; Holmes, Valerie A.; ,
Highlights: Women with GDM evaluated an educational DVD in a randomised controlled trial. The DVD did not affect maternal anxiety or blood glucose control. Intensive support women receive in specialist clinics may explain findings. Women were positive about the addition of the educational resource to usual care. Healthcare professionals could integrate the resource into patient education. Abstract: Aims: The diagnosis of gestational diabetes mellitus (GDM) during pregnancy can lead to anxiety. This study evaluated the impact of an innovative patient-centred educational DVD on anxiety and glycaemic control in women newly diagnosed with GDM. Methods: 150 multi-ethnic women, aged 19–44 years, from three UK hospitals were randomised to either usual care plus DVD (DVD group, n = 77) or usual care alone (control group, n = 73) at GDM diagnosis. Primary outcomes were anxiety (State-Trait Anxiety Inventory) and mean 1-h postprandial capillary self-monitored blood glucose for all meals, on day prior to follow-up. Results: No significant difference between the DVD and control group were reported, for anxiety (37.7 ± 11.7 vs 36.2 ± 10.9; mean difference after adjustment for covariates (95% CI) 2.5 (−0.8, 5.9) or for mean 1-h postprandial glucose for all meals (6.9 ± 0.9 vs 7.0 ± 1.2 mmol/L; −0.2 (−0.5, 0.2). However, the DVD group had significantly lower postprandial breakfast glucose compared to the control group (6.8 ± 1.2 vs 7.4 ± 1.9 mmol/L; −0.5 (−1.1, −<0.1; p = 0.04). Conclusions: The results in this trial did not highlight any differences between those who received the intervention and those who received usual care. It is possible that women already felt supported by their frequent attendance at specialist clinics for monitoring and advice. Healthcare professional and family support are key elements to empowering women with GDM and require further consideration in future interventions. Nonetheless, educational resources such as this will be beneficial to help support women given the current resource and time implications of the year on year rises in the incidence of gestational diabetes.